Analysis and measurement of harmonics in power system and power electronic circuits - Tun, Tun. (2011)
A new method of analysis is proposed to graphically predict the spectrum envelope of electromagnetic interference (EMI) emitted by power electronics equipment. Relationships between the time-domain (waveforms) and the frequency-domain (spectrum) of some typical EMI signals observed in power converters are pointed out. Special attention is paid to the analysis of the transient functions of EMI signals. It is shown they behave as filtering or “smoothing” functions in the high-frequency part of the spectrum.